1976
DOI: 10.1021/bi00665a011
|View full text |Cite
|
Sign up to set email alerts
|

Complete amino acid sequence of the myoglobin from the Atlantic bottlenosed dolphin, Tursiops truncatus

Abstract: The complete amino acid sequence of the major component myoglobin from the Atlantic bottlenosed dolphin, Tursiops truncatus, was determined by specific cleavage of the protein to obtain large peptides that are readily degraded by the automatic sequencer. Three easily separable peptides were obtained by cleaving the protein with cyanogen bromide at the 2 methionine residues and 4 peptides were obtained by cleaving the methyl acetimidated protein with trypsin at the 3 arginine residues. By subjecting 4 of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…As seen in Figure 3 Dali porpoise myoglobin has close similarities in sequence with various members of the family Delphinidae (dolphins). Dali porpoise myoglobin differs in sequence by only four residues from the identical sequences of the Atlantic bottlenosed dolphin (Jones et al, 1976) and Pacific common dolphin (Wang et al, 1977) myoglobins and by six residues from the sequences of pilot whale myoglobin (Jones et al, 1978) and killer whale myoglobin (Castillo et al, 1977). The sequence of Dali porpoise myoglobin will be compared here with that of pilot whale myoglobin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As seen in Figure 3 Dali porpoise myoglobin has close similarities in sequence with various members of the family Delphinidae (dolphins). Dali porpoise myoglobin differs in sequence by only four residues from the identical sequences of the Atlantic bottlenosed dolphin (Jones et al, 1976) and Pacific common dolphin (Wang et al, 1977) myoglobins and by six residues from the sequences of pilot whale myoglobin (Jones et al, 1978) and killer whale myoglobin (Castillo et al, 1977). The sequence of Dali porpoise myoglobin will be compared here with that of pilot whale myoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…All chemical modifications, enzymatic and chemical cleavages, and peptide fractionation procedures were as described previously (Dwulet et al, 1975;Bogardt et al, 1976;Jones et al, 1978).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequenator analysis of these fragments and the apomyoglobin provided over 80% of the covalent structure of the protein. The remainder of the primary structure was determined by further In preceding papers, the complete primary structure of the myoglobins from Amazon River dolphin (Dwulet et al, 1975), California gray whale (Bogardt et al, 1976), Atlantic bottlenosed dolphin (Jones et al, 1976), and Arctic minke whale (Lehman et al, 1977) were reported. All of these sequences of cetacean myoglobins were determined by automated Edman degradation.…”
mentioning
confidence: 99%